AB0506 GIANT CELL ARTERITIS: IS ROUTINE CLINICAL PRACTICE COMPREHENSIVE ENOUGH?. (2nd June 2020) - Martínez-Barrio, J.; Serrano Benavente, B.; Del Río Blasco, T.; Ariza, A.; Ovalles, J.; Molina Collada, J.; González, T.; Gonzalez, C.; Castrejon, I.; Alvaro Gracia, J. M.
Abstract : Background: Recommendations to collect the most relevant information on disease course, treatment and outcomes in giant cell arteritis (GCA) has been proposed by EULAR to facilitate clinical research and to improve clinical care. Objectives: To assess the quality of data collection in routine clinical practice according to EULAR recommendations and to describe baseline and follow-up characteristics of a retrospective cohort of patients with GCA. Methods: We reviewed medical records of patients diagnosed with GCA in a tertiary academic center between 2004-2018. We included patients with available data at diagnosis and one year of follow-up. Data extraction included: demographics, diagnosis, GCA-related signs and symptoms, laboratory, imaging modalities, comorbidities and treatment. Data in the chart was then compared with the core set of parameters proposed for GCA registries and databases by EULAR. Major relapse, according to the EULAR 2018 definition, was independently assessed by two rheumatologists. Results: 58 patients were identified, 39 met predefined inclusion criteria with 151 visits during first-year follow-up. Headache (100%; 80.4%), ocular symptoms (89.7%; 81.2%), constitutional symptoms (89.7%; 80.4%), polymyalgia rheumatica (89.7%; 82%) and jaw claudication (87%; 81.2%) were the most frequently collected items at baseline and follow-up. Weight and height (2.6%; 2.6%), peripheral pulses (8%; 4.5%), smoking status (41%; 21%), and blood pressure (61.5%; 4.5%) were the less frequently collected. Most patients lacked differential pressure measurement. Myocardial infarction, malignancy, serious infections, arterial hypertension, diabetes and osteoporosis were collected in every patient (39, 100%). Only 2 mayor relapses were identified (5%). Two (2) patients died during the one-year follow-up period. Table 1 provides information on GCA-related signs and symptoms, laboratory and therapeutic data. Conclusion: Although data collection in routine care is usually comprehensive enough according to EULAR proposed data set, key components in physical exam mostly those aiming to detect large vessel involvement, should be addressed more carefully. References: [1]Ehlers L, et al. Ann Rheum Dis. 2019;78(9):1160–6. [2]Hellmich B, et al. Ann Rheum Dis. 2019;1–12. Disclosure of Interests: Julia Martínez-Barrio Consultant of: UCB Pharma, Belén Serrano Benavente: None declared, Tamara Del Río Blasco: None declared, Alfonso Ariza: None declared, Juan Ovalles: None declared, Juan Molina Collada: None declared, Teresa González: None declared, Carlos Gonzalez Consultant of: Gilead, Janssen, Novartis, , Speakers bureau: Abbvie, Celgene, Gilead, Janssen, Novartis, Pfizer, Roche, Isabel Castrejon: None declared, Jose Maria Alvaro Gracia: None declared